The Algorithmic Goodbye: How AI is Reshaping End-of-Life Decisions - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The Algorithmic Goodbye: How AI is Reshaping End-of-Life Decisions The integration of Artificial Intelligence (AI) into healthcare is rapidly transformi...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Medical Ethics